Optimization of Samapta Unit Motor Vehicle Patrol in the Prevention of Motor Vehicle Theft at Pasuruan Police Station - Maisini, Michael Marcho (Advances in Police Science Research Journal, 2024)
This research was conducted with the aim of optimizing the patrol of the Samapta unit patrol unit in the context of preventing curanmor crime in the jurisdiction of the Pasuruan Regional Police. The author carries out research with a qualitative approach to the type of field research and data collection techniques through observation activities, interviews, and document studies. This research was conducted using the theory of routine activity, management (POAC) and analysis theory (SWOT) as the author’s analysis media. Facts on the ground show that patrol activities carried out by the Pasuruan Police patrol unit are still not optimal because the division of labor of patrol personnel is not clear and patrol operational standards are still not in accordance with the regulations set by the police chief. Based on the results of the analysis conducted by the author, the lack of optimal patrol activities is caused by the quantity of personnel that has not met the standards, causing the withdrawal of personnel from other units to meet patrol needs. In addition, the operational standards of the samapta unit in the implementation of patrols are not appropriate and need to be improved. Therefore, the author provides suggestions and inputs to the Pasuruan Police patrol unit to optimize motor vehicle patrols in the prevention of curanmor crimes, namely proposing additional personnel and utilizing GPS technology and social media that have developed to increase participation and attract public interest in the prevention of curanmor crimes.This research Hopefully, can be a guideline for the National Police, especially in the patrol unit of the samapta unit in the prevention of theft with aggravation in the jurisdiction of the Pasuruan Police Station. Keywords: Optimization, Patrol, Samapta Unit, Motor Vehicle Theft, Pasuruan Police Station.